The California wildfires, 2018 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Inc., 2020)
The people of northern California were used to living with the threat of wildfires. But nothing could have prepared them for the devastating 2018 fire season, the deadliest in 100 years and the most destructive in history.
Includes bibliographical references.
4.3
3-6
610L
Keywords: Wildfires -- California -- Juvenile fiction; Survival -- Juvenile fiction; Wildfires -- California -- Fiction; Fires -- Fiction; Survival -- Fiction; Historical fiction; Action and adventure fiction